A Tale of Two Transition Disks: Alma Long-Baseline Observations of Iso-Oph 2 Reveal Two Closely Packed Nonaxisymmetric Rings and a ∼2 Au Cavity - Perez-Marquez, S (IOP Publishing Ltd, 2020)
ISO-Oph 2 is a wide-separation (240 au) binary system where the primary star harbors a massive (M dust ∼ 40 M ⊕) ring-like disk with a dust cavity ∼50 au in radius and the secondary hosts a much lighter (M dust ∼ 0.8 M ⊕) disk. As part of the high-resolution follow-up of the "Ophiuchus Disk Survey Employing ALMA"(ODISEA) project, we present 1.3 mm continuum and 12CO molecular line observations of the system at 0.″02 (3 au) resolution. We resolve the disk around the primary into two nonaxisymmetric rings and find that the disk around the secondary is only ∼7 au across and also has a dust cavity (r ∼ 2.2 au). Based on the infrared flux ratio of the system and the M0 spectral type of the primary, we estimate the mass of the companion to be close to the brown-dwarf limit. Hence, we conclude that the ISO-Oph 2 system contains the largest and smallest cavities, the smallest measured disk size, and the resolved cavity around the lowest-mass object (M ∗ ∼ 0.08 M o˙) in Ophiuchus. From the 12CO data, we find a bridge of gas connecting both disks. While the morphology of the rings around the primary might be due to an unseen disturber within the cavity, we speculate that the bridge might indicate an alternative scenario in which the secondary has recently flown by the primary star causing the azimuthal asymmetries in its disk. The ISO-Oph 2 system is therefore a remarkable laboratory to study disk evolution, planet formation, and companion-disk interactions. © 2020. The American Astronomical Society. All rights reserved..